The asymmetric effects of exchange rate on trade balance of Vietnam - Loc Dong Truong; Dut Van Vo (Heliyon, 2023)
This study examines the asymmetric effects of exchange rate on Vietnam’s trade balance. Data used in this study consist of monthly trade balance, exchange rate, industrial production index and foreign direct investment series over the period from January 2010 to June 2020. Using the nonlinear autoregressive distributed lag (ARDL) bounds testing approach, the empirical findings confirm that the exchange rate has asymmetric effects on trade balance in both the long-run and short-run, meaning that a decrease in exchange rate has the different effect on trade balance as an increase in exchange rate with the same size. Specifically, in the short-run, one percent increase in the exchange rate (USD/VND) is associated with 4,2607% decrease in the trade balance, while appreciation of VND have no effects on the trade balance. In the long-run, one percent increase in the exchange rate results in 0.902% increase in the trade balance. However, no evidence is found for the effect of the appreciation of VND on the trade balance in the long-run. Moreover, the results derived from the error correction model (ECM) indicate that 89.07% of the disequilibria from the previous month are converged and corrected back to the long-run equilibrium in the current month.